Self-Management Program for Housing (PAV): some relevant aspects when thinking about the lives of women from low-income sectors in the Autonomous City of Buenos Aires - María Laura Gil y de Anso; Julia Ramos (Punto Género, 2012)
Buenos Aires city (Argentina) shares the latinamerican trend toward of the accelerated processof poverty urbanization, registering high levels of social exclusion and social spatial segregation.Specifically, in housing matter, and in spite of the assumed commitments, the public policiesthat the municipal government develops according to response to the housing problems,are insufficient, turning the women of low incomes into a particularly vulnerable group as aresult of the weight of their multiple roles, culturally constructed (productive, reproductiveand communitarian). Within this framework, the present article focuses, from a perspectivethat intercepts the concepts of gender and habitat, in the ‘Programa de Autogestión para laVivienda', of the Government of Buenos Aires city, as a result of its potentialities relative to thelife quality of women of popular sectors.